Construction Solutions for Reducing the Effect of the Rear-end Collision - Kertész, József; Kovács, Tünde (International Journal of Engineering and Management Sciences, 2022)
Analysing the accident statistics, we can detact that, the improvement of the transport safety is one of the most important engineering task. The number of the vehicles in the trasport gets significantly higher from year-to year, and the infrastructure of the cities frequently can not coordinate already it. Therefore the increasing of the vehicles’s number naturally involves the upgrowth of the accidents occasions too. The aim of the improvement of the vehicle-construction to reduce the personal injured and death resulted accidents number in contrast with the increasing traffic performance. This study analyses the construction options for reducing the effect of the rear-end collision whiches are concentrated for the passive vehicles and its passengers firtsly. Among the actual car manufacturers applied solutions, foward-looking possibilities and suggestions are described in this publication. The development can not be concentrated for only the safety improvement, the mass-optimalization must be completed simultenously. These apparent contrary requirements can be completed with application of new materials. Therefore the study addresses the more optimal utilization of the meatl foam in the vehicles crushbox. In addition, an optimized break-assist solution is described based on the Mercedes developed Pre Safe Plus® system to increas the abrorbtion of the impact energy.